The experiences of cancer nurses working in four European countries: A qualitative study. (December 2020) - Kelly, Daniel; Lankshear, Annette; Wiseman, Theresa; Jahn, Patrick; Mall-Roosmäe, Heleri; Rannus, Kristi; Oldenmenger, Wendy; Sharp, Lena
Abstract: Purpose: Cancer nurses across Europe are being tasked with delivery of an increasing number of complex treatments and supportive care interventions as a result of ongoing advances in cancer research, and a rise in cancer incidence due to demographic changes. However, all health systems delivering cancer treatment innovations require access to an educated and motivated nursing workforce to meet demand. This study by the European Oncology Nursing Society examines comparative features of cancer nursing in Estonia, Germany, the Netherlands (NL) and the United Kingdom (UK). Methods: Descriptive qualitative study using focus groups and individual interviews drawing on the views of cancer nurses, managers and stakeholders from four European countries (n = 97). Data collection was designed around national cancer nursing conferences held in Berlin (Germany), Ede (NL), Harrogate (UK) and Tallinn and Tartu (Estonia) between May 2017 and April 2018. Participants included a mix of nursing grades and specialisms. Findings: According to the participants education and career structure for cancer nursing was most well-developed in the Netherlands and the United Kingdom. In Germany and Estonia developments were taking place at Masters level. None of the countries had recordable qualifications in cancer nursing. Variations existed in terms of advanced practice roles and salary. Workload pressures were common, and were rising, and wellbeing initiatives were not identified. Nurses reported gaining positive feedback from caring for patients. Discussion: As demand for cancer treatment continues to grow there is a need to ensure an adequate supply of cancer nurses with the appropriate education and career structure to support patients. This study provides insights from four countries and suggests the need for better recognition as well as working conditions, education and career structures that advance the potential of the cancer nursing role in Europe. Highlights: Increasingly high nursing workloads are evident in Europe alongside workforce shortages. Major changes taking place in the treatment of cancer require more individualised and targeted treatment approaches. In some countries, cancer nurses adopt advanced roles that include prescribing, treatment co-ordination and clinical procedures. Comparative qualitative insights are provided concerning cancer nursing in Estonia, Germany, the Netherlands and the United Kingdom. Despite common European Union Directives disparities exist in the availability of cancer nursing education and working across EU countries.